10y-6=-8-y

Simple and best practice solution for 10y-6=-8-y equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 10y-6=-8-y equation:


Simplifying
10y + -6 = -8 + -1y

Reorder the terms:
-6 + 10y = -8 + -1y

Solving
-6 + 10y = -8 + -1y

Solving for variable 'y'.

Move all terms containing y to the left, all other terms to the right.

Add 'y' to each side of the equation.
-6 + 10y + y = -8 + -1y + y

Combine like terms: 10y + y = 11y
-6 + 11y = -8 + -1y + y

Combine like terms: -1y + y = 0
-6 + 11y = -8 + 0
-6 + 11y = -8

Add '6' to each side of the equation.
-6 + 6 + 11y = -8 + 6

Combine like terms: -6 + 6 = 0
0 + 11y = -8 + 6
11y = -8 + 6

Combine like terms: -8 + 6 = -2
11y = -2

Divide each side by '11'.
y = -0.1818181818

Simplifying
y = -0.1818181818

See similar equations:

| 0.5m+1=21 | | -2[-2(y+1)-3(y-2)]=8 | | 0.1(x+20)-5=0.25(2x+8) | | -26.25-15.5x=-15.5x+11.78 | | 6y-4=-8+10y | | 3x-5-5x=-13 | | N+4+9= | | X+28=x+x+2 | | c*5=30 | | -26.25-15.5x=-15.5+11.78 | | 6x^2+7-49=0 | | -8d+96=3d-3 | | 36=9x+6y | | 3/7=c+4/35 | | r^4+2r^3+10r^2+18r^1+9=0 | | 5k-4(k+4)=2 | | 0.625y+8=5+0.5y | | b+4/=7/4 | | y+8=14 | | 6m-3=2 | | 3g+2(-6+4g)=1-g | | (300+x)(1500+9x)=6 | | 3+x+5x=3 | | 6m-3=9 | | 179-5x=40x+24 | | -116=-4w | | 3x^2+14=-13x | | 3x+2=9x-4 | | 12-(4)(-2)= | | 4x-8=2x+22 | | 74=26+8v | | -6y+30=-45 |

Equations solver categories